Konsep Pendidikan Islam di Era Digital dalam Kitab Tarbiyah fi Zaman al-Fitan: Relevansinya bagi Generasi Digital Native - Zain Fuad Hariri (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2025)
The rapid advancement of digital technology has transformed learning patterns, social interactions, and character formation among the digital native generation, creating new challenges for Islamic education in nurturing faith, morality, and ethical values amid the widespread influence of digital information. This study aims to analyze the concept of Islamic education presented in Tarbiyah fi Zaman al-Fitan by Shaykh Ali bin Yahya al-Haddadi and examine its relevance to the character development of digital natives. Employing a qualitative library research approach with content analysis, the study uses the book as its primary source, supported by scholarly literature on Islamic education and digital generation studies. The findings indicate that the educational framework emphasizes the central role of parents as primary educators through gradual learning, the cultivation of strong Islamic faith, character development, and ethical conduct from an early age. These principles remain highly relevant in addressing contemporary digital challenges, including harmful online content, instant culture, declining family interaction, and cyberbullying. The study concludes that integrating Islamic educational values with the responsible use of digital technology offers a strategic framework for developing digitally competent individuals while strengthening their moral integrity and spiritual resilience.